1994
DOI: 10.1152/ajpregu.1994.267.5.r1371
|View full text |Cite
|
Sign up to set email alerts
|

Differential control of ventilation among inbred strains of mice

Abstract: The role genetic factors play in ventilatory control was examined by challenging eight inbred strains of mice to acute hypercapnia under normoxic and hypoxic conditions. Age-matched mice were exposed for 3-5 min to inspired gases of the following composition (FICO2:FIO2) 0.03:0.10, 2) 0.03:0.21, 3) 0.08:0.10, and 4) 0.08:0.21, with intermittent room air exposures. Breathing frequency (f) and tidal volume (VT) of unanesthetized, unrestrained mice were assessed by whole body plethysmography. During room air brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

24
142
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(170 citation statements)
references
References 0 publications
24
142
4
Order By: Relevance
“…Regardless of genotype, all animals responded to hypercapnia with an increase in minute ventilation (i.e., the product of respiratory frequency and tidal volume). The increase in ventilation observed with elevated inspired CO 2 was similar to that measured in studies of other wild type mouse strains (Tankersley et al, 1994), and there was no significant . RTN neurons from TASK channel knock-out mice retain pH sensitivity and express a pH-sensitive K ϩ current like their wild-type counterparts.…”
Section: Central Respiratory Chemosensitivity Is Retained In Task Knosupporting
confidence: 83%
“…Regardless of genotype, all animals responded to hypercapnia with an increase in minute ventilation (i.e., the product of respiratory frequency and tidal volume). The increase in ventilation observed with elevated inspired CO 2 was similar to that measured in studies of other wild type mouse strains (Tankersley et al, 1994), and there was no significant . RTN neurons from TASK channel knock-out mice retain pH sensitivity and express a pH-sensitive K ϩ current like their wild-type counterparts.…”
Section: Central Respiratory Chemosensitivity Is Retained In Task Knosupporting
confidence: 83%
“…They found significant inter-strain differences in ventilation during air breathing and in the ventilatory response to two chemical loadings, and these inter-strain differences might have been influenced by genetic determinants. The present study seemed to support partly the study by Tankersley et al (1994). Several mouse strains of the present study were the same as those used in Tankersley's study, such as DBA/2, BALB/c, C3H/He, C57BL/6 and A/J.…”
Section: Discussionsupporting
confidence: 81%
“…However, as the mice recovered from apnea after air breathing or the heart beat was recognized by touching, the apneic episodes during severe hypoxic loading could be expected to have occurred independently of near arrest. Tankersley et al (1994) studied the interstrain variance of the ventilatory response to normal air, hypoxia and hypercapnia among eight inbred strains of mice. They found significant inter-strain differences in ventilation during air breathing and in the ventilatory response to two chemical loadings, and these inter-strain differences might have been influenced by genetic determinants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphometric studies using mice are rare, but they have found significant differences in the airway morphometry of two murine strains with different genetic backgrounds (Oldham et al, 1994;Oldham and Robinson, 2007). Relevant differences in respiratory physiology have also been reported for different mouse strains and sexes (Tankersley et al, 1994;Reinhard et al, 2002;Flandre et al, 2003). In addition, structural and physiological alterations in mouse models of susceptibility as well as in genetically engineered mice may significantly influence inhaled particle deposition (Mall, 2008).…”
Section: Introductionmentioning
confidence: 99%